2019
DOI: 10.1002/ccr3.2191
|View full text |Cite
|
Sign up to set email alerts
|

Successful determination of nilotinib dosage by therapeutic drug monitoring in a patient with chronic myeloid leukemia developing hepatic dysfunction: A case report

Abstract: Fixed dosage regimen is currently the standard therapy with tyrosine kinase inhibitors (TKI). This case report demonstrates successful determination of nilotinib dosage by therapeutic drug monitoring (TDM) in a patient with chronic myeloid leukemia (CML). TDM may provide useful marker for individualized dosing of TKI for the treatment of CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We developed a rapid, sensitive, and efficient UPLC-MS/MS method to simul ously determine osimertinib, aumolertinib, and furmonertinib concentrations in hu Therapeutic drug monitoring (TDM) is an important technique for formulating dosing regimens for drugs with strong toxic effects, and great individual differences measured by drug concentrations in biological samples can identify inter-patient differences and improve the therapeutic effects of drugs while reducing AEs [22][23][24]. Several studies have also shown that TDM can improve the therapeutic efficacy of TKIs, supporting rational clinical use [25][26][27][28]. The ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method is a standard analytical tool for TDM and is widely used in clinical practice for precise treatment with targeted oral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a rapid, sensitive, and efficient UPLC-MS/MS method to simul ously determine osimertinib, aumolertinib, and furmonertinib concentrations in hu Therapeutic drug monitoring (TDM) is an important technique for formulating dosing regimens for drugs with strong toxic effects, and great individual differences measured by drug concentrations in biological samples can identify inter-patient differences and improve the therapeutic effects of drugs while reducing AEs [22][23][24]. Several studies have also shown that TDM can improve the therapeutic efficacy of TKIs, supporting rational clinical use [25][26][27][28]. The ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method is a standard analytical tool for TDM and is widely used in clinical practice for precise treatment with targeted oral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Better management consists of therapeutic drug monitoring (TDM). Nakahara et al 3 from Japan reported a successful dose of Nilotinib adjustment after hepatic dysfunction grade 3.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since its approval in 2007, Nilotinib has emerged as a second-generation TKI (2G TKI) with antileukemic activity remarkably effective and reasonably safe medication for the treatment of CML. 2,3 We report the case of a patient with CML who developed unfortunately life-threatening liver toxicity secondary to Nilotinib. Actually, European LeukemiaNet (ELN) recommends adapting treatment choices according to patient history and comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported a case report of successful determination of nilotinib dosage by TDM in a patient with CML developing hepatic dysfunction. 21 The safety and efficacy of imatinib for CML have been reviewed. 22 Maintaining an optimal trough plasma imatinib concentration is important for ensuring maximum efficacy in patients with CML.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TDM of TKIs is an important tool for CML treatment. We have previously reported a case report of successful determination of nilotinib dosage by TDM in a patient with CML developing hepatic dysfunction 21 . The safety and efficacy of imatinib for CML have been reviewed 22 .…”
Section: Discussionmentioning
confidence: 99%